MIR4435-2HG as a possible novel predictive biomarker of chemotherapy response and death in pediatric B-cell ALL - Torres-Llanos, Yulieth; Zabaleta, Jovanny; Cruz-Rodriguez, Nataly; Quijano, Sandra; Guzmán, Paula Carolina; de los Reyes, Iliana; Poveda-Garavito, Nathaly; Infante, Ana; Lopez-Kleine, Liliana; Combita, Alba Lucía (Frontiers in Molecular Biosciences, 2024)
Introduction: Although B-cell acute lymphoblastic leukemia (B-cell ALL) survival rates have improved in recent years, Hispanic children continue to have poorer survival rates. There are few tools available to identify at the time of diagnosis whether the patient will respond to induction therapy. Our goal was to identify predictive biomarkers of treatment response, which could also serve as prognostic biomarkers of death, by identifying methylated and differentially expressed genes between patients with positive minimal residual disease (MRD+) and negative minimal residual disease (MRD-). Methods: DNA and RNA were extracted from tumor blasts separated by immunomagnetic columns. Illumina MethlationEPIC and mRNA sequencing assays were performed on 13 bone marrows from Hispanic children with B-cell ALL. Partek Flow was used for transcript mapping and quantification, followed by differential expression analysis using DEseq2. DNA methylation analyses were performed with Partek Genomic Suite and Genome Studio. Gene expression and differential methylation were compared between patients with MRD−/− and MRD+/+ at the end of induction chemotherapy. Overexpressed and hypomethylated genes were selected and validated by RT-qPCR in samples of an independent validation cohort. The predictive ability of the genes was assessed by logistic regression. Survival and Cox regression analyses were performed to determine the association of genes with death. Results:DAPK1, BOC, CNKSR3, MIR4435-2HG, CTHRC1, NPDC1, SLC45A3, ITGA6, and ASCL2 were overexpressed and hypomethylated in MRD+/+ patients. Overexpression was also validated by RT-qPCR. DAPK1, BOC, ASCL2, and CNKSR3 can predict refractoriness, but MIR4435-2HG is the best predictor. Additionally, higher expression of MIR4435-2HG increases the probability of non-response, death, and the risk of death. Finally, MIR4435-2HG overexpression, together with MRD+, are associated with poorer survival, and together with overexpression of DAPK1 and ASCL2, it could improve the risk classification of patients with normal karyotype. Conclusion:MIR4435-2HG is a potential predictive biomarker of treatment response and death in children with B-cell ALL.